Domestication of Avena magna Murphy et Terrell: a wild tetraploid oat species endemic of Morocco - N. Saidi; N. Shaimi; A. S. Idrissi; A. Souihka; F. Gaboun; C. Al Faiz; G. Ladizinsky (Труды по прикладной ботанике, генетике и селекции)
Avena magna Murphy et Terrell (2n = 4x = 28), a tetraploid oat species endemic of Morocco, has a high groat protein content (more than 20%), good resistance to diseases and good adaptability to the Mediterranean edaphic and climate conditions. Moreover, this taxon is morphologically similar to the hexaploid oat species A. sativa and promising for interspecific crosses with A. sativa in order to transfer the domestication syndrome into it. Four hybridization cycles employing four accessions of A. magna and five Moroccan hexaploid oat cultivars of A. sativa were accomplished to domesticate A. magna. Morphological characterization and cytogenetic analysis of derivative hybrid seeds were made to determine their ploidy level and select the seeds with 2n = 28. The overall combinations yielded 81 hybrid plants with 2n varying from 28 to 29, with 58% having 2n = 28, and pollen fertility over 85%. However, 27 hybrids yielded a seed set ranging from 20 to 80%. Selected hybrid plants were subjected to pedigree selection in the field until they reached the 8th generation and assessed for agronomic performance. Three domesticated lines of tetraploid oat A. magna were selected for their good disease resistance. Analysis of groat protein content in the selected hybrids using the Kjeldahl method showed that it was 2 to 3% higher than in their parents.